The Role of OmpR in the Expression of Genes of the KdgR Regulon Involved in the Uptake and Depolymerization of Oligogalacturonides in Yersinia enterocolitica - Nieckarz, Marta; Raczkowska, Adrianna; Jaworska, Karolina; Stefańska, Ewa; Skorek, Karolina; Stosio, Dorota; Brzostek, Katarzyna (Frontiers in Cellular and Infection Microbiology, 2017)
Oligogalacturonide (OGA)-specific porins of the KdgM family have previously been identified and characterized in enterobacterial plant pathogens. We found that deletion of the gene encoding response regulator OmpR causes the porin KdgM2 to become one of the most abundant proteins in the outer membrane of the human enteropathogen Yersinia enterocolitica. Reporter gene fusion and real-time PCR analysis confirmed that the expression of kdgM2 is repressed by OmpR. We also found that kdgM2 expression is subject to negative regulation by KdgR, a specific repressor of genes involved in the uptake and metabolism of pectin derivatives in plant pathogens. The additive effect of kdgR and ompR mutations suggested that KdgR and OmpR regulate kdgM2 expression independently. We confirmed that kdgM2 occurs in an operon with the pelP gene, encoding the periplasmic pectate lyase PelP. A pectinolytic assay showed strong upregulation of PelP production/activity in a Y. enterocolitica strain lacking OmpR and KdgR, which corroborates the repression exerted by these regulators on kdgM2. In addition, our data showed that OmpR is responsible for up regulation of the kdgM1 gene encoding the second specific oligogalacturonide porin KdgM1. This indicates the involvement of OmpR in the reciprocal regulation of both KdgM1 and KdgM2. Moreover, we demonstrated the negative impact of OmpR on kdgR transcription, which might positively affect the expression of genes of the KdgR regulon. Binding of OmpR to the promoter regions of the kdgM2-pelP-sghX operon, and kdgM1 and kdgR genes was confirmed using the electrophoretic mobility shift assay, suggesting that OmpR can directly regulate their transcription. We also found that the overexpression of porin KdgM2 increases outer membrane permeability. Thus, OmpR-mediated regulation of the KdgM porins may contribute to the fitness of Y. enterocolitica in particular local environments.